Radiocarbon ages for sediment core EN22502 from Salmon Lake, Alaska - Darrell S Kaufman (PANGAEA, 2025)
Radiocarbon (14C) ages were measured on 49 samples of macrofossils extracted from a sediment core extending back to roughly 30,000 calendar years before present (cal yr BP) from Salmon Lake, on Seward Peninsula, northwest Alaska. The 16.7-m-long core was collected in August 2022 by the Alfred Wegener Institute, Potsdam, Germany in collaboration with Northern Arizona University (NAU), Flagstaff, USA. The 14C ages were combined with age constrains from short-lived isotopes to generate an age-depth model (doi:10.1594/PANGAEA.984002) for the core using rBacon software. It serves as the timeline for sediment samples from the core, which have been used for a large suite of biological, geochemical and physical analyses.